Stigma Masyarakat Terhadap Mantan Narapidana (Studi Kasus Kecamatan Ganra Kabupaten Soppeng) - Rahmi, Muthiah; Tahir, Heri; Sakka, Abdul Rahman A. (Universitas Negeri Makassar, 2021)
The study aims to discover: (i) the causes of community stigma on former convicts in Ganra subdistrict in Soppeng district, (ii) the social interaction of the community with former convicts in Ganra subdistrict in Soppeng district, and (ii) public acceptance of former convicts in Ganra subdistrict in Soppeng district. This research is a type of qualitative research by using purposive sampling technique as to obtain the informants. Ten informants were used in this study according to the needs of the researcher by determining the criteria of the informants. Data collection techniques employed observation, interview, and documentation to obtain concrete data relating to the problems of the research. The data validity technique in this study employed source triangulation technique. Based on the results of the study, it shows that there are three findings: (i) the occurrence of stigma by the community on former convicts there are two, namely the attitude of former convicts who tend to be closed and the existence of social stigma in society